INTENSITAS PENGGUNAAN ELECTRONIC BANKING OLEH NASABAH PT. BANK CENTRAL ASIA CABANG UTAMA AMBON - Pary, Gilman (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2017)
The purpose of this research is to test the effect of consumers value and system quality toward trust in order to increase frequency of the use of internet banking. The sample in this research are 180 BCA consumer as respondent. The technique used in this research was purposive sampling. Certain characteristics means only for consumer whose at least one product connected with electronic banking facility and using electronic banking facility in financial and non financial transaction for above 6 months. Structural Equation Modelling (SEM) run by AMOS software, used to analyze the data. The analysis result shows that consumer value and system quality effected on trust in order to increase the use of internet banking. This empirical result indicates that consumers value have significant effect toward trust, system quality have significant toward trust, and trust have significant toward the use of internet banking.